Pelatihan Metode Pembelajaran Sains Untuk Satuan Pendidikan: Pelatihan Metode Pembelajaran Sains Untuk Satuan Pendidikan - MA Muazar Habibi (Postgraduate Program, University of Mataram, 2024)
Abstract: This science competency development program is an initiative aimed at the community, with a focus on enhancing science literacy understanding among early childhood education (ECE) educators. This activity was prompted by the insufficient level of science literacy among ECE teachers. It employed an interactive methodology that included discussions, question-and-answer sessions, as well as direct practices and simulations of science activities, conducted at the Lenterahati Islamic Boarding School in West Lombok, NTB. The program's participants included a manager and three educators as partners. Before commencing the training sessions, a needs analysis was conducted to determine the materials and training models to be tailored to the needs and capacities of the partners. The results of this program indicated a positive response from the participants towards the implementation of science learning methods, as evidenced by their active involvement in asking questions and discussing challenges faced during the learning process. From this activity, there was an improvement in the knowledge and skills of teachers in understanding and applying concepts and practices of science learning in early childhood education settings